Evaluation of scrotal reconstruction with thigh flap - Islam, Md Tarikul; Dey, Palash Kumar; Kamal, Abu Hena Mustafa; Uddin, Md Farid (Bangladesh Medical Journal Khulna, 2018)
Background: Scrotal skin can be lost in many ways. Partial loss of scrotum is easy to manage but major scrotal skin loss represents a significant challenge to the reconstructive surgeon. Although many techniques have been established for the treatment of major scrotal defects, each technique has its own advantages and disadvantages in specific situations. Objective: The aim of this prospective study was to evaluate the outcome of thigh fascio-cutaneous flap for reconstruction of major scrotal loss with exposed testis. Methods: This prospective study was done for 5 years extending from January 2012 to December 2016. In this period we reconstructed major scrotal defects of eight patients with antero medial and pudendal thigh fascio-cutaneous flap in Burn and Plastic Surgery department, Khulna Medical College Hospital. Total eleven thigh fascio-cutaneous flaps were used for reconstruction of major scrotal defects. Results: The mean patient age was 41 years (range 24 to 62 years). The aetiology of scrotal loss was Fournier's gangrene in 4 cases and trauma in 4 cases. Three cases had bilateral and five cases had unilateral flap reconstruction. The flaps allowed sensate coverage and took well. Primary donor site closure obviated the need for skin grafts in most of the cases, Complications were flap tip necrosis (12.50%) and minor wound infection (12.50%) which were treated conservatively. Donor site scar was limited and acceptable. The flap had good aesthetic appearance except in one fatty patient where the flaps were bulky. Conclusion: The study concluded that thigh fascio-cutaneous flap is very reliable for coverage of major scrotal defects. Bang Med J (Khulna) 2017; 50 : 13-17